Naming and disrupting epistemic injustice across curated sites of learning. Issue 2 (15th March 2022) - Stroupe, David
ABSTRACT: Curated sites of learning—places that are created by people to promote formal and informal knowledge and knowledge production practices (such as schools and museums)—are deemed foundational by many societies in assisting children to become knowers. However, curated sites of learning can also uphold ways of knowing that can cause harm to people marginalized from knowledge production, which philosophers describe as epistemic injustice. By looking across fields of research (education and philosophy), I describe how epistemic injustice can be utilized in education research to provide a shared analytical lens for examining curated sites of learning. I name four levels of interaction in which epistemic injustice can occur given their purposeful design by people with power: moment-to-moment interactions, micro (within a site), meso (between local sites) and macro (between sites and national/international policies and rhetoric). I describe how educators and researchers might disrupt epistemic injustice through the examination of curated learning sites and their personal ideas about knowledge. I also highlight tensions and dilemmas that might arise for educators and researchers when engaged in such work.